COMMUNITY PERCEPTIONS OF FIRE PREVENTION AND FIRE MANAGEMENT EFFORTS IN A DENSELY POPULATED RESIDENTIAL AREA FOLLOWING A MAJOR FIRE: A STUDY OF DR. SUTOMO STREET, ALLEY 8, SAMARINDA CITY - Najwa Kumala Dewi; Nurul Kamaliah Umasangaji (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Residential fires are among the most frequent disasters occurring in densely populated urban areas and often generate significant social, economic, and environmental impacts. This study aims to analyze community perceptions of fire prevention and fire management efforts in Dr. Sutomo Street, Alley 8, Sidodadi Village, Samarinda Ulu District, Samarinda City. A qualitative approach with a case study design was employed to gain an in-depth understanding of community experiences, knowledge, and perceptions regarding fire risk. Research participants consisted of officers from the Samarinda City Fire Department, neighborhood leaders, and residents affected by fire incidents, who were selected through purposive sampling. Data were collected through semi-structured interviews, observations, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings indicate that the community holds positive perceptions of government-led fire prevention programs, including public awareness campaigns, training on the use of portable fire extinguishers (APAR), the establishment of Fire Volunteers (Redkar), and the PRO-BEBAYA Program. The major fire incident in 2024 emerged as the primary factor shaping community risk perceptions and increasing awareness of the importance of preparedness. Enhanced preparedness is reflected in the availability of fire-fighting equipment at both household and neighborhood levels, improved community capacity to undertake initial fire response actions, and high levels of participation in fire mitigation activities. Nevertheless, the study area remains highly vulnerable due to building density, the predominance of wooden houses, narrow access roads, and limited water resources. This study concludes that fire experience, community knowledge, and community-based mitigation programs play a crucial role in shaping risk perception and community preparedness. These findings contribute to the advancement of risk perception studies within the disaster context and provide a basis for strengthening community-based fire mitigation policies in densely populated urban residential areas.